Resources mobilized in nursing preceptorship: a study in Grounded Theory - Marques da Silva Amaral, Guida Maria; Simões Figueiredo, Amélia (O Mundo da Saúde, 2022)
The development of skills implies the mobilization of resources considering personal learning, educational training, and professional experience. The quality of skills depends on the combination of personal resources and the environment. The objective of this study was to identify the resources that are mobilized in the development of competencies of nursing preceptors. A qualitative study was carried out based on Grounded Theory. The study took place in two services of a hospital in the metropolitan area of Lisbon, from November 2018 to December 2019. The interviews were carried out with nurses at different stages of Patrícia Benner’s Socio-Professional Development Model and with different experiences in guiding nursing students. Theoretical sampling was conducted according to the needs identified in the data coding. Data analysis and treatment was performed according to the Grounded Theory methodology. The resources mobilized in the development of preceptor nurses’ competencies were characterized as endogenous and exogenous. Endogenous refers to individual characteristics, skills, and experiences. The exogenous characteristics are the Nursing team and the teacher. Nurses, supported by the Nursing team, mobilize individual characteristics and skills in their skill development as preceptors. The identification of these resources can define indicators for a preceptor profile and contribute to the training of preceptor nurses.